ALGORITMA MENENTUKAN HIMPUNAN TERBESAR DARI SUATU MATRIKS INTERVAL DALAM ALJABAR MAX-PLUS - Novitasari, Ratna (MATEMATIKA, 2011)
This research discussed about how to obtained largest set from an interval matrix if given a possible eigen vector. For obtained the largest set, we would doing some iteration and then determined the best algorithm.